G314(P) A rare neurological cause of limping and hip dysplasia. (12th March 2018) - Butt, A; Sinha, G
Abstract : Introduction: Limping is a common presentation in children. It has many aetiologies, from trauma, infection, haematological conditions and malignancies. We would like to present a rare cause of limping. Syringomyelia describes a longitudinal fluid cavity of the spinal cord, whether a dilatation of the central canal or cavitation of the grey matter. There is a paucity of data, particularly of paediatric cases. Clinical manifestations depend on the location and size of the syrinx. They typically involve segmental signs, with wasting of the small muscles of the hand, sensory deficits and absence of tendon reflexes. It can also cause lower limb spasticity, and a loss of pain and temperature sensation. Case report: A previously fit and well 18 month girl was referred with a 3 month history of dragging the left foot and limping. The mother's pregnancy and child's neonatal period was uneventful. Her growth was between the 9th-25th centile, and developmental milestones were appropriate. She was passing urine normally, and was constipated for 4 months. On initial assessment she was noted to have birth marks on her lumbar spine. She had normal tone, power and reflexes in both lower and upper limbs. She had no wasting of the small muscles of the hands. Her left foot appeared to be larger than the right, and when walking she was dragging her left foot. At this point the parents were advised how to manage the constipation and the child was sent for physiotherapy, hip X-rays and MRI of the brain and spine. The hip X-ray showed mild loss of coverage of the left femoral head. The cranial MRI was normal. MRI without contrast showed a cystic abnormality in the conus medullaris most likely due to Syringomyelia; MRI contrast excluded spinal tumour. The radiologist felt the abnormal development of the left hip could be secondary to the syrinx, or evolution of developmental dysplasia. Learning points/conclusion: This case highlights the need for full examination, and appropriate investigation of the spine, hips, abdomen and lower limb from a musculoskeletal and neurological perspective.